Nursing process model application in Malaysian nursing education / Lynn Lynn Thet - Lynn, Lynn Thet (2017)
A mixed method survey was conducted in four Malaysian public and one private universities from September to December, 2015. The purpose of this study is to identify the current status on the implementation of Nursing’s Agenda Four which is the implementation of Nursing Process Model (NPM) application in Malaysian nursing context. Therefore, this study illuminates the status on the implementation of NPM which reflects how the future of Malaysian Nursing will be expected by the Department of Higher Education. The Department of Higher Education expects that all employers of new nursing graduates have minimum four basic nursing competencies, to be referred to as Key Performance Indicators (KPI) by 2016 through implementing NPM application from 2010 onward. Therefore, the study objectives are mainly focused on the extent of success in the implementation process in terms of investigating their level of knowledge about NPM, the attitude towards NPM, its application and implementation process and their impression towards the factors that support in the implementation of NPM application. The researcher also investigates the factors influencing in the implementation process, and interpret the respondents’ opinions concerning NPM and the factors that promote or hinder on the implementation of NPM application in learning theory and performing practice. The convenient sample composed of Heads of Department (HODs) and academic staffs with different positions (n = 50) and student nurses (n = 486). Two sets of adapted questionnaire which combined closed-ended questions for quantitative and open-ended questions for qualitative inquiry. The findings of quantitative inquiry by using multiple regressions show that the student nurses’ gender and different study modes were not significant predictors on their practice of NPM, whereas their extent of knowledge, attitude and their impression towards supporting factors are significant predictors in their practice of NPM. The mediation analysis reveals the supporting factors is mediating in relation between knowledge and practice which indicates that supporting factors play an important role while turning knowledge of NPM into application in Malaysian nursing context. In addition, the HODs and academic staffs’ gender and their different positions in the department were not the significant predictors upon their attitude and impression towards supporting factors which indicates whether they are male or female, clinical instructor or tutor or lecturer or HODs, they have the same attitude and impression towards supporting factors. While triangulating with the findings of qualitative inquiry by using qualitative content analysis support the findings of quantitative inquiry. Conclusively, the attitude in terms of internal factors show more driving forces rather than resisting, whereas the external supporting factors are needed to improve in terms of management support, adequate resources, to create balance nurse patient ratio which affect the workload and time available of nurses, to upgrade the documentation system to reduce much paper work, to aware of teamwork and collaboration among health care professionals, to aware the importance of motivation and effective monitoring and evaluation system within the implementation context, to aware to conduct workshops, seminars, and continuing nursing education program especially paying attention to NPM application. Furthermore, intra and interprofessional awareness and collaboration are also needed to make other health care professionals to aware about this change process and implementing policy which is the application of NPM.